Association of physical functioning of persons with dementia with caregiver burden and depression in dementia caregivers: an integrative data analysis. (4th May 2019) - Armstrong, Nicole M.; Gitlin, Laura N.; Parisi, Jeanine M.; Roth, David L.; Gross, Alden L.
ABSTRACT: Objectives: To determine whether caregiver relationship and race modify associations between physical functioning of persons with dementia (PWD) and their caregiver's burden and general depressive symptoms. Method: We pooled data from four behavioral intervention trials ( N = 1, 211). Using latent growth modeling, we evaluated associations of PWD physical functioning with the level and rate of change in caregiver burden and caregivers' general depressive symptoms and stratified these associations by caregiver relationship and race. Results: PWD were, on average, 81 years old (68% female) with mean follow-up of 0.5 years. More baseline PWD physical impairment was associated with less worsening in caregiver burden over time (β = −0.23, 95% CI: −0.29, −0.14), but this relationship was not modified by caregiver characteristics. More impaired baseline PWD physical functioning was not associated with changes in depressive symptoms (β = −0.08, 95% CI: −0.17, 0.00), but was associated with less worsening in depressive symptoms among spousal (β = −0.08, 95% CI: −0.17, 0.00) and non-white (β = −0.08, 95% CI: −0.17, 0.00) caregivers. Conclusions: Dementia caregivers may experience reduced caregiver-related burden because of adjustment to PWD functional status, while spousal and non-white caregivers may experience less depressive symptoms resultant of adjustment to functional status.